(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The purpose of the study is a systematic analysis of the functions, instruments and role of the Bank of Russia as a mega-regulator in the context of structural transformation of the economy. The paper examines the key areas of monetary and macroprudential policy, identifies mechanisms for managing systemic risks and ensuring financial stability. The practical significance lies in the possibility of using the research results by public authorities, credit institutions and analytical structures to assess the effectiveness of regulation and adaptation to external shocks.